Pengembangan Bahan Ajar Pintar dan Cepat Berhitung Perkalian Siswa Sekolah Dasar - Hifna Irodatut Thoyyibah; M.Yusuf Setia Wardana; Singgih Adhi Prasetyo (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The context that informs this research is Participation in Mathematics lessons, especially lessons related to multiplication, is less enthusiastic for some students, the teaching materials used are still very minimal because teachers only use teaching materials such as educator books and student books where the student books are less interesting visually on teaching materials used in low grades, especially grade II, there are no pictures and variations that can stand out for students, educators still have difficulties in making teaching materials. The objectives of this research are the development, validity, and feasibility of Smart and Quick Count Multiplication for Elementary School Students. The research method used is the Research and Development method with the ADDIE development model. The subject of this research is a class II student at SD Negeri Yosorejo. The results showed that the average of the material expert's question sheet was 99%, the media expert's question sheet was 99%, the student response question sheet was 99% and the teacher's response question sheet was 91% which means very good. That way, grade II students at SD Negeri Yosorejo can utilize smart teaching materials and quickly count multiplication.